Feed the Future Myanmar Agriculture Policy Support Activity - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
The International Food Policy Research Institute (IFPRI), in partnership with Michigan State University, is undertaking a collaborative program called the Feed the Future Myanmar Agriculture Policy Support Activity (MAPSA) with the financial support of the United States Agency for International Development (USAID). This activity will support the government in a time of rapid (yet uneven) transition by: establishing the foundations for long-term growth by improving agriculture sector governance; building the capacity of key stakeholders to prioritize and implement strategic organizational and policy reforms; and facilitating broad stakeholder participation in policy dialogue and advocacy. MAPSA activities will focus on the administrative areas that are the geographical focus of USAID: Kachin State, Mandalay Region, Magway Region, Shan State, and Sagaing Region. Reliable data are a basic requirement for effective design and monitoring of market-led economic reforms in the agriculture sector that will help to balance regional trade and investment so as to address the historical inequalities in livelihoods and nutrition status between ethnic communities that underpin conflict. Analysis of the data will also provide an understanding of how agriculture, gender, and nutrition linkages affect nutritional outcomes.